Cognitive dualism, ontological dualism, and the question of God. (20th June 2019) - Ellis, Fiona
Abstract: Cognitive dualism offers a defensible conception of theism, and Scruton is right to endorse it. However, he retains a commitment to the ontological dualism it is his purpose to reject, and this leads to a deep tension in his position which leaves him unable to make sense of there being a route to the Divine. I argue that this tension stems from a residual commitment to a Kantian framework, and that this framework is not mandatory. I propose an alternative model which is compatible with much of what Scruton says, but which offers a more consistent and satisfactory theistic picture.